Types of Meaning in the Heuras Genggerong Karawang T-Shirt Design - Roni Nugraha Syafroni, (Proceeding of International Conference on Language Pedagogy (ICOLP), 2024)
The background of this research is that linguistics turns out to be intertwined with things outside the language itself. The creative industry designs typical Karawang T-shirts. Then, the researcher combines linguistics to analyze the T-shirt design of the Heuras Genggerong Karawang T-shirt manufacturer. The importance of this research is to find out the type of meaning of the Heuras Genggerong T-shirt design. Examples of some designs from Heuras Genggerong include several tourist attractions in Karawang, special event in Karawang, and social condition in Karawang, totaling 10 T-shirt designs. The researcher analyzed the design of these T-shirts by downloading from the official Instagram account of @distro_heuras_genggerong, by utilizing the theory of types of meaning. The objectives of this study is to find out the relationship between the utilization of type of meaning theory in T-shirt design. The method of this research is descriptive analysis. The findings this research analyzed the design of these T-shirts by downloading from the official Instagram account of @distro_heuras_genggerong, by utilizing the theory of types of meaning. The conclusion of this research is that the type of meaning theory contained in the design of Heuras Genggerong T-shirts can be analyzed using the theory of types of meaning.